IMPLEMENTASI PROMOSI KESEHATAN TENTANG MENJAGA KEBUGARAN FISIK USIA LANJUT DI RW 05 DESA JAYARAGA KECAMATAN TAROGONG KIDUL GARUT - Iin Patimah; Tantri Puspita; Rudy Alfiyansah; Eldessa Vava Rilla; Hasbi Taobah Ramdani; wahyudin; Engkus Kusnadi; Andhika Lungguh Perceka (LP4M STIKes Karsa Husada Garut, 2020)
The health status of the elderly is not as good as at a young age. Often the elderly suffer from various diseases that generally occur due to decreased organ function. Based on the initial study we conducted in RW 05 Jayaraga Village, Tarogong Kidul Garut District, there were 80 elderly, 30 women and 50 men. Of the 80 elderly, there are 40 elderly who frequently visit Pos Bindu, and 20 elderly who experience health problems such as hypertension and gout. The activity of the elderly is to always come every month to the bindu post to have their health checked. The objectives of this community service are: providing an understanding of maintaining fitness in old age, health education for the elderly and preventing disease in old age. The methods used in this community service are: Lecture method on maintaining fitness in old age, and demonstration method in the form of gymnastics for the elderly. The target of this activity is the elderly with a total of 80 people. The urgency of this community service activity is that old age is seen as a period of decline, a period where the elderly feel a decrease in the decline that occurs in them both physically and psychologically. Some elderly people still view old age with an attitude that shows hopelessness, is passive, weak and dependent on relatives. The elderly do not have enough effort to develop themselves so that the elderly experience deterioration both physically and mentally. So it can be concluded so that it can be concluded that the implementation of these activities has been going well. It can be seen from the results that participants can understand and respond to the material we convey and participants can do elderly exercise.